Unraveling sources of hydrocarbons in subtropical estuaries with distinct degrees of protection in the Southwestern Atlantic Ocean, Brazil - Martins, César C.; Moreira, Lucas Buruaem [UNESP]; Sutilli, Marina; de Souza Abessa, Denis Moledo [UNESP] (Elsevier, 2023)
Sedimentary aliphatic hydrocarbons and polycyclic aromatic hydrocarbons (PAHs) were studied in subtropical estuaries with distinct degrees of legal protection, located in the Southwestern Atlantic Ocean, São Paulo State, Brazil. A multivariate approach was adopted, using the Hierarchical cluster analysis followed by the Principal Matrix Factorization analysis to support the hydrocarbons sources findings using diagnostic ratios. In general, the sites with the highest values of hydrocarbons were in the vicinity of well-urbanized cities, where sewage discharge, harbor and industrial activities take place. Pyrolitic PAHs were the predominant source of PAHs in the sites. The region can be considered not highly contaminated by hydrocarbons; however, specific sites under local anthropogenic impact from sewage and/or urban drainage, presented relatively high hydrocarbons levels. These findings highlight the importance of sources identification as reliable approach to be included in the management plan of protected areas under the inputs of several vectors of contamination.
Keywords: Contamination; Environmental risk; Mangrove; Marine protected areas; Sediment; Sewage outfall